Effect of taurine on renal pathophysiology in Experimental animals - Dr. LAISHRAM ELIZABETH DEVI; Dr. VICTORIA LAISHRAM; Dr.USHAM DHAMARAJA MEETEI; Dr. ASTHOMI JAMOH (International Journal of Pharma and Bio Sciences, 2016)
Taurine, an essential amino acid (2-amino ethanesulfonic acid) and endogenous antioxidant agent has been studied as an antioxidant agent in renal impairment however the efficacy is not very well documented and its impact on exogenous supplementation in normal renal physiology has conflicting results. Therefore the present study has been undertaken to evaluate the role of Taurine supplementation in normal physiology and impaired kidney status due to high dose Diclofenac in rat models. Albino rats were divided into groups of 4 animals each. Test I(Diclofenac only), Test II( Taurine only), Test III(Diclofenac + Taurine), Test IV(Diclofenac + Taurine + N-acetylcysteine). Diclofenac 13.5mg/kg bw/day i.m. given for 10 days. Taurine(7.5mg/kg/day) and N-acetycysteine(NAC(40 mg/kg) were given orally for 2 wks starting from day 5 of induced nephrotoxicity in respective groups. Serum urea and creatinine levels were measured after 1wk and 2wks of test drug administration and histopathological examination conducted. High dose of Diclofenac i.m. produced biochemical and histopathological features of nephrotoxicity. Biochemical and histopathological parameters also revealed features of nephrotoxicity in taurine only treated group. The group treated with Taurine + NAC for 2wks had significantly lowered nephrotoxic features compared to only Taurine treated group in nephrotoxic models.